2005
DOI: 10.1016/j.virol.2004.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the neutralizing antibody response elicited in rabbits by repeated inoculation with trimeric HIV-1 envelope glycoproteins

Abstract: The elicitation of broadly neutralizing antibodies directed against the human immunodeficiency virus type 1 (HIV-1) envelope glycoproteins, gp120 and gp41, remains a major challenge. Attempts to utilize monomeric gp120 as an immunogen to elicit high titers of neutralizing antibodies have been disappointing. Envelope glycoprotein constructs that better reflect the trimeric structure of the functional envelope spike have exhibited improved immunogenicity compared with monomeric gp120. We have described soluble g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
93
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 41 publications
8
93
1
1
Order By: Relevance
“…The neutralization of primary HIV isolates using sera from rabbits immunized with proteoliposomes bearing YU-2 Env trimers has recently been reported (16). Proteoliposome immunization resulted in enhanced neutralization of primary isolates compared with that induced by soluble gp120 alone, similar to findings in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The neutralization of primary HIV isolates using sera from rabbits immunized with proteoliposomes bearing YU-2 Env trimers has recently been reported (16). Proteoliposome immunization resulted in enhanced neutralization of primary isolates compared with that induced by soluble gp120 alone, similar to findings in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Several strategies to address this, including the use of soluble gp140 trimers (23,38,39,42,49), solid-phase proteoliposomes incorporating oligomeric Env (16,17), and HIV-1 pseudovirions (19,31,37), are under investigation. Pseudovirions are viruslike particles (VLPs) that are capable of exhibiting the native Env trimer on their membrane surface.…”
mentioning
confidence: 99%
“…It is possible that immunizing with an immunogen with better CD4-binding properties would result in more potent VHH. Previous studies have shown that purified trimeric envelope proteins are somewhat better at eliciting cross-subtype-neutralizing antibodies than monomeric recombinant gp120 (6,7,22,32,38,90). We are currently screening llamas immunized with recombinant trimeric gp140.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent vaccine experiments have shown that DNA expressing unmodified HIV-1 Env proteins can elicit low-level antibodies that neutralize the homologous primary isolate (2). Low-titer cross-reactive neutralizing antibodies have been elicited using modified envelope DNA vaccines or recombinant proteins (2,17,25,39). Because the assays used and viruses tested have differed from study to study, it is difficult to compare the results directly.…”
Section: Discussionmentioning
confidence: 99%